” TEXTBOOK) METHODOLOGY OF WORKING WITH LITERARY TEXTS IN GENERAL SECONDARY SCHOOLS (BASED ON 6TH GRADE “LITERATURE - Egamberdiyeva Nilufar (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This scientific article analyzes the methodology of working with literary texts in the process of teaching literature in general secondary schools. In particular, based on the texts of the 6th grade “Literature” textbook, it highlights ways to develop students’ literary thinking, form text analysis skills, and the effectiveness of using interactive methods.